The spatial ecology and behaviour of the broadnose sevengill shark (Notorynchus cepedianus) in South Africa - Engelbrecht, Tamlyn (Department of Biological Sciences, 2025)
Top predators are an important component of healthy ecosystems, contributing to ecosystem stability and biodiversity through direct and indirect effects. However, significant knowledge gaps exist in our understanding of the occurrence, biology and spatiotemporal dynamics of marine predators, limiting our ability to conserve these species in the face of anthropogenic threats. The broadnose sevengill shark (Notorynchus cepedianus) is a marine top predator with a global distribution in coastal and shelf waters of temperate regions. This species faces exploitation across their range and are classified as “Vulnerable” on the IUCN Red List of Threatened Species. In this thesis, the distribution, growth rates, spatiotemporal dynamics and habitat use of N. cepedianus in the coastal waters of southern Africa were investigated. Firstly, the distribution and growth rate of N. cepedianus in southern Africa were investigated using data from the Oceanographic Research Institute's Cooperative Fish Tagging Project. Broad-scale patterns in coastal presence, movement and population connectivity were then investigated for both sexes and a range of sizes of N. cepedianus in South Africa using acoustic telemetry, and a national scale array of acoustic receivers (the Acoustic Tracking Array Platform). Finally, an array of acoustic receivers in False Bay, Cape Town, were used to investigate patterns in the presence and fine-scale movement patterns of N. cepedianus in False Bay. During data collection, several unexpected predations on N. cepedianus by killer whales (Orcinus orca) occurred in False Bay, providing a unique opportunity to investigate the impacts of a novel apex predator on the behaviour of N. cepedianus. Overall, the results showed that N. cepedianus has a broad distribution in temperate coastal waters of southern Africa, ranging from northern Namibia to the Eastern Cape Province of South Africa. Growth rates for N. cepedianus at reference lengths of 100 cm and 160 cm (PCL) were estimated to be 4.7 cm.year-1 and 4.0 cm.year-1 , respectively, which are slower than previous growth estimates for this species. Population connectivity was established between the west and south coasts of South Africa, but not between South Africa and Namibia. Tag recapture data and acoustic telemetry showed that N. cepedianus of all sizes display site fidelity to certain coastal sites, and most movements had a limited range (<50 km). However, a few individuals of both sexes and a range of sizes made large-scale coastal movements of up to 600 km, highlighting that a portion of the population roams more widely. Acoustic telemetry also confirmed size and sex segregation by N. cepedianus at coastal sites in southern Africa. These findings can be used in stock assessments and to guide spatial management for this species. Within False Bay, most female N. cepedianus showed high site fidelity to Miller's Point, a large, well-known aggregation site for this species, and were observed returning for up to four consecutive years after extended periods of absence. However, following O. orca predation events, tagged N. cepedianus fled the site within 24 hours for up to 290 days. There was a notable decrease in the number of N. cepedianus that returned to Miller's Point following each of the four confirmed predation events by O. orca, until eventually, the sharks abandoned the aggregation site completely. Displacement of a top predator (N. cepedianus) by an even higher-level predator (O. orca) is expected to have cascading effects on ecosystems, highlighting the need to monitor impacts to better understand the ecological role of sharks and the consequences of population declines.